Effects of Cyclophosphazene Derivatives on Malondialdehyde, Glutathione and Total Protein Content in Yeast Culture Media - Ozsahin, Ayse Dilek; Beser, Derya; Ozturk, Ali Ihsan; Aslan, Fatih; Yilmaz, Okkes (Kahramanmaras Sutcu Imam Univ Rektorlugu, 2020)
In this study; total protein, glutathione and lipid peroxidation (MDA) analyzes of five schiff bases that are newly synthesized were performed in S. cerevisiae culture media. YEPD medium was prepared for growth and multiplication of S. cerevisiae. Overall, 10 mg/mL and 20 mg/mL concentrations of schiff bases were added for the creation of application groups in to the culture medium. The obtained supernatant was used for total protein, glutathione (GSH), oxidized-glutathione (GSSG) and MDA analyzes. When the results of the control and schiff groups were compared; newly synthesized schiff bases in S. cerevisiae was determined to increase total protein, GSH and MDA concentration. As a conclusion, it is thought that newly synthesized schiff bases will support the future studies that will be carried out the antioxidant defense effect and cytotoxic properties and it is thought that will contribute to the literature.
Keywords: Glutathione; MDA; Saccharomyces cerevisiae; Schiff bases; Total Protein